2008
DOI: 10.12693/aphyspola.113.1293
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Interaction with Vacancies in Electron Irradiated Niobium

Abstract: Defect studies of Nb irradiated with 10 MeV electrons were performed in the present work by means of positron annihilation spectroscopy. The lattice defects were characterized by positron lifetime spectroscopy. Moreover, defect depth profiles were studied by slow positron implantation spectroscopy. The experimental investigations were accompanied by first principles theoretical calculations of positron parameters. It was found that irradiationinduced vacancies in Nb specimens are surrounded by H, which causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 15 publications
2
16
1
Order By: Relevance
“…This is a larger value in comparison to other metals, for instance in Cu it is equal to 121(7) nm [13] and in stainless steel 73.7(1.7) nm [27]. Nevertheless, this value coincides with data from the literature, Č ížek et al reported even higher value, i.e., about 319(8) nm [17]. For the sample exposed to dry sliding with the load of 50 N the determined values are equal to: S int = 0.493(1), S surf = 0.515 (1), and the positron diffusion length: L ?…”
Section: Positron Beam Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…This is a larger value in comparison to other metals, for instance in Cu it is equal to 121(7) nm [13] and in stainless steel 73.7(1.7) nm [27]. Nevertheless, this value coincides with data from the literature, Č ížek et al reported even higher value, i.e., about 319(8) nm [17]. For the sample exposed to dry sliding with the load of 50 N the determined values are equal to: S int = 0.493(1), S surf = 0.515 (1), and the positron diffusion length: L ?…”
Section: Positron Beam Resultssupporting
confidence: 77%
“…In fact, in the positron lifetime spectrum measured for virgin samples, only one lifetime component equal to 129(1) ps was resolved. This value coincidences with the value reported in the literature, i.e., 128.3(3) ps for positron annihilation in bulk [16,17].…”
Section: Sample Preparationsupporting
confidence: 91%
“…Typical sputtering parameters are summarized in Table 3.1. Two different orientations of sapphire substrate, (0001) and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) supplied by Crystec GmbH were used to investigate probability of different growth orientation. Some specified conditions will be described on each result.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In Fig. 3.3 a simulated example of XRR curve of a V 100-nm thick film on a Al2O3 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) substrate capped by Pd 20-nm thick film is shown. The simulation was done by IMD developed by Windt [Windt98].…”
Section: Xrrmentioning
confidence: 99%
See 1 more Smart Citation